Impact: Assessing the outcomes of IFPRI's research - Yosef, Sivan; Zandstra, Tamsin; Place, Frank; Babu, Suresh Chandra (International Food Policy Research Institute, 2025)
Food policy research plays an essential role in helping to achieve food security for all, promote sustainable and healthy diets, build efficient markets, transform economies, and strengthen food systems institutions and governance. This chapter examines IFPRI’s impacts over the last 50 years through providing independent, high-quality evidence to inform policy options, programs, and investments.